Foreign language for specific purposes at higher medical establishments - Tregub, S.; Трегуб, Світлана Євгенівна (National Technical University of Ukraine “Igor Sikorsky Kyiv Polytechnic Institute”, 2019)
Changes in the system of medical education, its reformation and integration into the international educational space require an increase in the efficiency of the training process and the quality of the medical specialist training. In our opinion, one of the improving aspects of a future doctor’s professional training is the knowledge of professional foreign lexics, possession of such kind of speech activity as a reading not only in the context of academic education, but also for the special purposes, for example, when preparing for a special licensed exam “Step-1,2,3”. Thus, the knowledge of "professional medical English terms", the basics of the word formation of medical terms, the possession of the suffixes and prefixes meaning, questioning sentences, and the TE of Latin will allow medical students not only to create both an active and passive vocabulary, but also significantly increase their potential in English professional literature translating.
Keywords: professional medical text; professional English